Study on HIV/AIDS knowledge, sexual attitudes, sexual behaviors, and preventive services among young students in Chongqing, China - Qing, Liyuan; Wang, Yunna; Yang, Tong; Chen, Xinrui; Zhang, Meng; Bu, Qingqing; Tan, Bo; Deng, Dan (Frontiers in Public Health, 2022)
Objectives This study aimed to describe the HIV/AIDS knowledge, sexual attitudes, and sexual behaviors of young students (14–25 years) in Chongqing, China, and to examine their use of preventive services and related factors. Method A cross-sectional study was conducted with students from 67 schools from December 2019 to June 2021. The chi-square test, non-parametric test to assess the differences between respondents with different characteristics in the above aspects. Additionally, univariate and multivariate logistic regression analyses were conducted to examine factors associated with the awareness of HIV/AIDS knowledge. Confidence intervals without crossover or P < 0.05 was considered significant. Results A total of 31,782 participants were included in the study. A total of 62.62% of the respondents were considered to be aware of basic HIV/AIDS knowledge, including 78.44%, 62.15%, and 52.08% in undergraduate colleges, junior colleges and secondary vocational schools, respectively. In total, 60.96% of males and 29.42% of females accepted premarital sex, 15.49% of males and 6.18% of females reported being sexually experienced, and only 57.18% of the students used condoms every time they had sex. The percentage of condom use among students who were aware of HIV/AIDS knowledge was higher than that among students who were not aware. A total of 85.60% of the students thought they needed HIV/AIDS prevention and control knowledge, and 94.60% thought more health education activities on HIV/AIDS prevention needed to be conducted in schools. Entrance education, lectures or consultation hotlines, WeChat official accounts and other media platforms were rated as the most acceptable HIV/AIDS prevention education methods. Conclusion These respondents lacked knowledge about HIV/AIDS, and an increasing number of students show an open attitude toward premarital sex and engage in risky sexual behaviors. It is urgent to enhance and widely disseminate comprehensive HIV/AIDS and sexual health education in multiple formats.